Association of sST2 with liver function in patients with acute heart failure related hospitalization - Zhenyi Liu; Ying Wang; Yuanyuan Song; Xiuyong Yu; Hanxin Yao (Frontiers in Cardiovascular Medicine, 2026)
Objective This study aimed to investigate the association between serum soluble ST2 (sST2) and liver injury biomarkers in patients with acute heart failure (AHF), and to evaluate the potential value of sST2 in identifying liver injury in AHF. Methods A total of 134 patients with AHF (with or without liver injury) were prospectively enrolled, along with 187 age- and sex-matched healthy controls. Serum sST2 were measured within 24 h of hospital admission, along with comprehensive clinical and laboratory assessments. Univariate and multivariate linear regression analyses were performed to explore the relationships between sST2 and liver function parameters. ROC curve analysis was used to evaluate the discriminative ability of sST2 for liver injury. Results Univariate analysis showed that sST2 had weak but statistically significant correlations with NT-proBNP ( r = 0.20), TBIL ( r = 0.26), and GGT ( r = 0.19), moderately weak correlations with DBIL ( r = 0.32) and ALP ( r = 0.35), and strong correlations with AST ( r = 0.71) and ALT ( r = 0.55) (all P < 0.05). No significant association was observed between sST2 and cTnI ( r = 0.07, P = 0.485). In multivariate regression, NT-proBNP (β = 0.001, P = 0.009), AST (β = 0.230, P < 0.001), and DBIL (β = 1.028, P = 0.003) were identified as independent predictors of sST2. Patients with liver injury had significantly higher sST2 levels ( P = 0.002). ROC analysis demonstrated that sST2 predicted liver injury with an AUC of 0.691, which was superior to NT-proBNP (AUC = 0.545). The combined model of sST2, AST, and DBIL yielded an AUC of 0.905, with a sensitivity of 85.2% and a specificity of 85.0%. Conclusion Serum sST2 is strongly associated with liver injury markers, particularly AST and DBIL, in patients with AHF. Elevated sST2 is associated with underlying hepatic dysfunction and may serve as a potential biomarker linking cardiac decompensation and liver impairment. Although sST2 alone has limited sensitivity for liver injury, a combined panel of sST2, AST, and DBIL provides excellent diagnostic performance. This combined approach may serve as a useful tool for risk stratification and early identification of cardiogenic liver injury.